Disintegrin Tablysin-15 Suppresses Cancer Hallmarks in Melanoma Cells by Blocking FAK/Akt/ERK and NF-ΚB Signaling - Deng, Zhenhui; Zeng, Qingye; Chai, Jinwei; Zhang, Bei; Zheng, Wenhong; Xu, Xueqing; Wu, Jiguo (Current Cancer Drug Targets, 2020)
Background: Integrins are crucial anti-cancer therapy targets. We previously showed that tablysin-15 is an integrin antagonist with its Arg-Gly-Asp motif in a novel structural context. Objective: Here we investigated the anti-cancer effects and mechanisms of action of tablysin-15 in melanoma cells. Methods: Cell adhesion, competitive binding, cell viability, and ATP chemiluminescence assays were used to analyze the binding of tablysin-15 to αvβ3 integrin and its phenotypic effects. Wound healing, transwells, and zymography were performed to detect motility and matrix metalloproteinase- 2/-9 activities. PARP and caspase-3 cleavage were used as apoptosis assays, while LDH release and flow cytometry were used for necrosis and cell cycle analysis. The expression of mRNAs and proteins of target molecules was measured by qRT-PCR and western blotting, respectively. Results: Tablysin-15 dose-dependently inhibited the proliferation, migration, and invasion of M21 cells through integrin αvβ3. The proliferation inhibition caused by tablysin-15 was attributable to G0/G1 phase arrest rather than apoptosis or necrosis. Furthermore, tablysin-15 suppressed MMP-2/- 9 activities and the mRNA expression of MMP-2/-9 and COX-2 but was upregulated TIMP-1 in M21 cells. Meanwhile, tablysin-15 suppressed the expression of cyclin D1/E and CDK 2/6, the phosphorylation of FAK, Akt, and ERK, and nuclear translocation of NF-ΚB, while increasing the expression of the CDK inhibitor p21waf1/C1. Taken together, tablysin-15 might inhibit melanoma cell metastasis and proliferation by competing with αvβ3 integrin, thereby blocking FAK-associated signaling pathways and nuclear translocation of NF-ΚB. Conclusion: Tablysin-15 has reliable anti-cancer effects against M21 melanoma cells, suggesting tablysin-15 is a promising anti-tumor drug.
Keywords: NF-ΚB